UPAYA MENINGKATKAN KEMAMPUAN MENULIS ILMIAH MAHASISWA S1 FISIOTERAPI UMS DENGAN METODE KOLABORASI PADA TAHUN AKADEMIK 2012/2013 - Rahmawati, Laili Etika; Thalia, Najma (Jurnal Penelitian Humaniora, 2012)
The aims of the research were (1) to apply the collaborative method to improve the academic writing skills of the students; and (2) to improve the academic writing skills of the students through the collaborative method. The type of the research were Classroom Action Research (CAR). The research activity started with the real problems faced by the lecturer in the teaching and learning process followed by the real actions which were measurable. The subjects of the research were the students of S1 Physiotherapy program, Health Science Faculty of Muhammadiyah University of Surakarta in the firstÂ semester of the academic year 2012/2013 who were taking the Indonesian subject. The result of the action research shows that by applying the collaborative method, the academic writing skills of the students were improved. This could be seen from their active participation in the classroom and their awareness of the importance of writing skill. The test result indicates the average score was 74, 43, with the maximum score was 97 and the minimum score was 47. The average score of the academic writing before given the actions was 53, 82 with the maximum score was 89 and the minimum score was 25. The average score after the actions increased significantly. It was concluded that the academic writing skills of the students were improved after taught using collaborative method.